The Effect of Stimulation Using Fetal Development Stickers Booklet on the Accuracy of Antenatal Care Follow-Up Visits for Pregnant Women - Fitriani, Henny; Sulistiawati, Rini; Rosita, Desy (Poltekkes Kemenkes Surakarta, 2025)
Background: Antenatal Care (ANC) service standards recommend that pregnant women undergo at least six medical check-ups during pregnancy: one in the first trimester, two in the second trimester, and three in the third trimester. However, ANC revisit rates in Indonesia remain suboptimal. This study aims to determine the effect of stimulation using a fetal development sticker booklet on the accuracy of ANC revisits among third-trimester pregnant women. Methods: This quasi-experimental study employed a one-group pretest-posttest design with control group. A total of 60 respondents were selected using purposive sampling and divided into treatment and control groups, with 30 participants each. The intervention involved affixing fetal development stickers representing fetal growth based on gestational age in the third trimester. The analysis used was the chi-square test. Results: The results showed a significant increase in on-time ANC revisits in the treatment group (83.3%) compared to the control group (36.7%). The test revealed a statistically significant relationship between the provision of fetal development stickers and ANC revisit accuracy, with a p-value of <0.001 (<0.05), Odds Ratio (OR) of 8.6, and a 95% Confidence Interval (CI) of 2.5–29.07. Conclusion: This indicates that pregnant women who were given fetal development stickers in their KIA books had an 8.6 times greater chance of making timely ANC visits compared to those who were not given stickers. Therefore, fetal development sticker booklets are an effective tool to improve ANC revisit compliance and can serve as a valuable complement to the standard Maternal and Child Health (MCH) handbook.